Batch and semi-continuous anaerobic co-digestion of goose manure with alkali solubilized wheat straw: A case of carbon to nitrogen ratio and organic loading rate regression optimization. (April 2017) - Hassan, Muhammad; Ding, Weimin; Umar, Muhammad; Rasool, Ghulam
Highlights: Development of C/N and OLR regression optimization models. Methane enhancement up to 96.10% due to C/N optimization. 20–30 is the optimum C/N range for AD of goose manure and wheat straw. 71.19% lignin removal due to NaOH solubilization of the wheat straw. Optimum OLR of 3 g.VS/L.d at C/N of 25 during CSTR experimentations. Abstract: The present study focused on carbon to nitrogen ratio (C/N) and organic loading rate (OLR) optimization of goose manure (GM) and wheat straw (WS). Dealing the anaerobic digestion of poultry manure on industrial scale; the question of optimum C/N (mixing ratio) and OLR (daily feeding concentration) have significant importance still lack in literature. Therefore, Batch and CSTR co-digestion experiments of the GM and WS were carried out at mesophilic condition. The alkali (NaOH) solubilization pretreatment for the WS had greatly enhanced its anaerobic digestibility. The highest methane production was evaluated between the C/N of 20–30 during Batch experimentation while for CSTRs; the second applied OLR of (3 g.VS/L.d) was proved as the optimum with maximum methane production capability of 254.65 ml/g.VS for reactor B at C/N of 25. The C/N and OLR regression optimization models were developed for their commercial scale usefulness.